iPhone - Hart-Davis, Guy (John Wiley & Sons, Inc., 2025)
iPhone For Dummies, 2025 Edition, covers the iPhone basics, as well as the features of iPhone 16 and earlier models. You'll also learn how to navigate the new iOS 17 release to make phone and FaceTime calls, send texts and messages, get online, play games, shoot video, and all the other amazing things your Apple smartphone can do. Guy Hart-Davis, a longtime Apple expert and Dummies tech author extraordinaire, shows you how to set up your phone to work with your life. Customize your settings, including privacy and app permissions, and make sure your phone is protected. Connect the new iPhone models to your other devices, sync your data from your previous phone, and learn about the new stuff you can do with updated hardware on the latest models. This beginner-friendly book makes it easy to become an iPhone power user. Whether this is your first iPhone or your umpteenth, iPhone For Dummies is the must-have resource for using your new device to its fullest.
Includes index
Keywords: iPhone (Smartphone); Smartphones; Cell phones; Portable computers; iPhone (Téléphone intelligent); Téléphones intelligents; Téléphones cellulaires; cellular telephones